Learning Visual Basic .NET - Stephens, Rod (Infinite Skills, 2014)
In this Visual Basic .NET ( VB.NET ) training course, expert author Rod Stephens will teach you how to program from scratch with Visual Basic. You will start by learning how to install and use the Visual Studio development environment. Rod will then teach you how to build classes that define properties, methods, and events in VB.NET, as well as understand and use overloaded methods and operators and perform calculations. This video tutorial will also cover topics including debugging programs, working with data types, branching and looping statements, and use subroutines, functions, and object-oriented techniques. You will learn how to use LINQ to select, modify, and sort information, as well as easily read and write data in files. Finally, you will learn about printing and print previews. Once you have completed this VB.NET training course, you will be fully capable of programming with Visual Basic.NET. Working files are included, allowing you to follow along with the author throughout the lessons.
Online resource; Title from title screen (viewed July 10, 2014)
Keywords: Electronic videos